Pembaharuan Substansi Hukum Pengadaan Tanah yang Berkeadilan - Ade Arif Firmansyah (Kanun Jurnal Ilmu Hukum, 2014)
Land is one of the important natural resources for humanbeing sustainability. Relation both of them is not only a place for life, but also it is providing resources for life. Thus, the government policy on land for development must be managed wisely today and for future. The policy includes also life provision for development. One of the government actions, the provision of it must be fair. It based on the principle that it must be protected by law, right to property or right of having it guaranteed by the constitution. Both for the owner and people in real cultivate the land without having certain rights given by the constitution will be protected. The Reform of Legal Substances of Fair Land Provision